Hyperbaric or hypobaric chambers? - Zinn, L.
Triathletes have always been interested in maximizing the body's potential to deliver performance. This urge is at the heart of the semi-annual migration of triathletes between Boulder and San Diego. Boulder offers thinner and perhaps cleaner air, while San Diego offers warmth in the winter and ocean swimming. Conventional wisdom has long held that the increase in red blood cells from living in Boulder will bring better results during the season; this is one reason that Boulder has long attracted elite runners and cyclists as well as triathletes. What performance benefits (or detriments) could you expect form adjusting your altitude? Take some time to sit and read and maybe you could save yourself some moving expenses this spring. Lately, a lot of attention has been paid to the work of University of Colorado Professor Igor Gamow. Gamow is best known to triathletes as the brains behind two inventions designed to create "virtual" altitude extremes, either quite high or quite low. Indeed, many triathletes have invested thousands in either the "Gamow Bag," a hyperbaric chamber (also marked under the name OXY AT, a licensee of Gamow's patent), or the "Gamow Bed," a hypobaric chamber, which respectively increase the decrease the air pressure around the user. There are claims of great benefits by users of both; what is the difference, and why use one or the other?